Earned Credit Could be Lost Credit - Amy Jo Richardson; David B. Knight (SAGE Publishing, 2024)
Beginning the path to a bachelor's degree in community college has the potential to be a more cost-effective higher education option. Previous research on transfer students has focused broadly on curriculum alignment, articulation policies, and academic advising in efforts to reduce credit loss. Credit loss can significantly impact transfer students and result in unnecessary time and costs for them. Minimal research quantifies and visualizes credit loss or explains in detail how and why it occurs throughout students' entire education trajectories. This study visualizes credit loss for bachelor's programs seeking engineering transfer students who began at in-state community colleges using data from the sending and receiving institutions. Findings revealed that credit loss can occur throughout the entire degree pathway, including high school dual enrollment and advanced placement credits to community college credits. This work has implications for informing degree pathways and policies that promote successful transfer and degree completion.